Individual differences influence exercise behavior: how personality, motivation, and behavioral regulation vary among exercise mode preferences - Allyson G. Box; Yuri Feito; Chris Brown; Steven J. Petruzzello (Heliyon, 2019)
Personality traits, participatory motives, and behavior regulation have been linked to physical activity engagement. It is possible that these dimensions are associated with the type of physical activity one chooses to engage. Thus, the purpose of this study was to examine individual differences in those participating in various primary modes of physical activity (PMA) and determine which individual differences are predictive of exercise frequency. Methods: 403 adults (36.3 ± 11.6 yrs, 35.5% male) completed an online survey. The survey included questions related to their PMA, items for the Big Five Inventory (BFI), Exercise Motivation Inventory (EMI-2), and the Behavioral Regulation in Exercise Questionnaire (BREQ-3). PMAs were divided into 5 main groups: CrossFit® Training (n = 89), Group Exercise (n = 59), Aerobic Training (n = 97), Resistance Training (n = 127), and Sport (n = 31). Results: A multivariate ANOVA revealed significant differences in exercise motivation [ps ≤ .001, η2p = .05 – .22] and behavior regulation [ps ≤ .05, η2p = .03 – .06] between PMAs, but personality dimensions did not differ. A linear regression revealed that differences in motivation and regulation explained 17.1% (p = .001) variance in exercise behavior. Conclusions: These findings support the notion that individual differences exist between motivational dimensions and individuals' preference to engage in a particular physical activity mode. Further, these differences in motivation influence physical activity engagement (i.e., frequency).